A home for Mr. Emerson - Kerley, Barbara (Scholastic Press, 2014)
Before Ralph Waldo Emerson was a great writer, he was a city boy who longed for the broad, open fields and deep, still woods of the country, and then a young man who treasured books, ideas, and people. When he grew up and set out in the world, he wondered, could he build a life around these things he loved? This biography illustrates the rewards of a life well-lived, one built around personal passions: creativity and community, nature and friendship.